2021
DOI: 10.1177/09544062211003601
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of nonlinear functionally graded piezoelectric energy harvester subjected to multi moving oscillators

Abstract: In this paper, energy harvesting from nonlinear vibration of a functionally graded beam covered by a piezoelectric patch under multi-moving oscillators is studied. The material of both the substructure and the piezoelectric patch is assumed to be functionally graded in the thickness direction. A coupled system of equations considering Euler-Bernoulli beam theory and von-Karman nonlinearity as well as electromechanical coupling are derived using the generalized Hamilton’s principle. Finite element method as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…On the other hand, research works have reported formulations focused on the improvement of the modelling accuracy of nonlinear vibrating structures with piezoelectric elements using the FE method, but do not consider for an external electrical circuit [23]. Additionally, studies investigated the energy harvested from the piezoelectric materials attempting to accurately model the general problem [24][25][26]. Lee and Inman [24] developed an analytical model of a bistable piezoelectric plate based on the classical lamination theory along with the experimental validation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, research works have reported formulations focused on the improvement of the modelling accuracy of nonlinear vibrating structures with piezoelectric elements using the FE method, but do not consider for an external electrical circuit [23]. Additionally, studies investigated the energy harvested from the piezoelectric materials attempting to accurately model the general problem [24][25][26]. Lee and Inman [24] developed an analytical model of a bistable piezoelectric plate based on the classical lamination theory along with the experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…Although they report a nonlinear component of the stiffness matrix, they do not assume any nonlinearity in the piezoelectric matrices, as the current work presents in the next section. Fatehi et al [26] utilized the FE method to solve a coupled nonlinear system of equations, considering Euler-Bernoulli beam theory and von-Karman nonlinearity, to study the performance of a nonlinear functionally graded piezoelectric energy harvester. With few exceptions, the majority of detailed FEA models for bistable piezoelectric harvesters are limited to strips and beams.…”
Section: Introductionmentioning
confidence: 99%